2021
DOI: 10.3390/su13116137
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Nutritional Quality Attributes and Their Inter-Relationship in Maize Inbred Lines for Sustainable Livelihood

Abstract: The present investigation was planned to understand the variability and inter-relationship among various nutritional quality attributes of maize kernels to identify potential donors of the respective traits for future hybridization programs. Sixty-three maize inbred lines were processed for the estimation of protein, starch, fat, sugar, 100-kernel weight, specific gravity, and moisture level of the grain. The results reveal that a wide variability among protein, starch, 100-kernel weight, specific gravity, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 19 publications
4
7
0
Order By: Relevance
“…Cluster VI is characterized of 12.92% of protein and test weight of 16.0 g. The protein content in lines decreased dramatically as the test weight of kernels increased. Therefore Selection of greater protein-containing lines without lowering test weight, as well as lines with higher values for both features, are given priority in breeding programmes there is a negative correlation between protein content and seed size (Saxena et al 1984), but in maize, a similar trend is observed in the current study, correlating with the results of Langyan et al (2021). Kernels of teosinte are very small but have higher protein content.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Cluster VI is characterized of 12.92% of protein and test weight of 16.0 g. The protein content in lines decreased dramatically as the test weight of kernels increased. Therefore Selection of greater protein-containing lines without lowering test weight, as well as lines with higher values for both features, are given priority in breeding programmes there is a negative correlation between protein content and seed size (Saxena et al 1984), but in maize, a similar trend is observed in the current study, correlating with the results of Langyan et al (2021). Kernels of teosinte are very small but have higher protein content.…”
Section: Discussionsupporting
confidence: 83%
“…Partially similar results were observed by Jio et al (2021), who reported a negative correlation between protein quality and kernel and yield traits. Additionally, protein content has a non-signi cant negative relationship with the test weight, validating the work ofLangyan et al (2021). In pulses,…”
supporting
confidence: 60%
“…The multivariate analysis, particularly PCA and HCA, are used to reduce the dimensions, identify traits that have maximum contribution in variability, and understand the relationships between germplasm lines ( 50 , 51 ). Several workers have reported PC1 has 1.3-fold higher Eigen values than that of PC2, which is commensurate with our findings of Eigen values of 3.232 (PC1) and 2.458 (PC2) ( 51 – 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…The quality of protein and its type is important to determine its overall health impact upon consumption ( 1 , 2 ). Protein provides energy, and it is also a vital component for other purposes, including enzyme activity and bio-chemicals passage in cellular membranes ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%